Corporate Demand for Reinsurance: Evidence from the United Kingdom Motor Reinsurance Market - Zhang, Ximeng (2012)
A substantial number of studies have researched the corporate demand for reinsurance but very few of them have looked into the motor reinsurance market. This dissertation employs a panel data analysis to undertake an empirical investigation into the UK motor reinsurance market in attempt to test whether certain determinants, expressed in related hypotheses, have influences over the demand for motor reinsurance. This dissertation finds that the motor reinsurance price is negatively unit elastic to the demand for the motor reinsurance whereas the motor insurance gross claim, the group membership, and the total asset are positively correlated to the demand for the motor reinsurance.